Optimal Contracts Allocation Using Mean Variance Optimization Method - Azevedo, Filipe (2017)
The process of restructuration and liberalization of power systems are a constant all over the world. However, those processes, due to the specific characteristics of the “product” electricity, create uncertainty and new risks that did not exist when power systems were vertically integrated. Those changes origin the necessity of tools that allow the participants of the electricity markets to practice the hedge against the volatility of the System Marginal Price. In that sense, we present in this paper a decision-support application, based on a Mean Variance Optimization Method trying to give a response to the necessities of the electricity markets participants. The results show that the proposed method can be useful to producers and also to others participants of electricity markets like Brokers and Load Serving Entities (LSE).